The Challenge of the Transition to Renewable Energies: A Geopolitical Approach in the Light of the International Competition for Rare Earth Elements - Zerniz, Amal (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2024)
This article aims to analyze the geopolitical dimensions of the transition to renewable energies in light of the international competition over securing access to rare earth elements (REEs), referred to as new geopolitical foundations that give the countries possessing them a geopolitical advantage. The study addressed three elements representing the geopolitics of REEs in renewable energy supply chains, global economic powers’ strategies to ensure access to them based on China’s dominant position in their markets as well as the geopolitics of international competition to secure access to REEs. The article concluded that the rising demand for REEs sparks a worldwide “mineral war,” in which global economic powers line up to secure access to these strategic resources necessary to build a future for clean energy. However, challenges remain significant and complex given their interconnection with the current international energy security mechanisms after many regions with large REEs reserves have become theatres of geopolitical tensions. Niniejszy artykuł ma na celu analizę geopolitycznych wymiarów przejścia na odnawialne źródła energii w świetle międzynarodowej konkurencji o zabezpieczenie dostępu do metali ziem rzadkich (REE), określanych jako nowe fundamenty geopolityczne, które dają krajom je posiadającym przewagę geopolityczną. Badanie dotyczyło trzech elementów reprezentujących geopolitykę REE w łańcuchach dostaw energii odnawialnej, strategii globalnych potęg gospodarczych mających na celu zapewnienie dostępu do nich w oparciu o dominującą pozycję Chin na ich rynkach, a także geopolityki międzynarodowej konkurencji o zabezpieczenie dostępu do REE. Artykuł zakończył się wnioskiem, że rosnący popyt na REE wywołuje światową „wojnę mineralną”, w której globalne potęgi gospodarcze ustawiają się w kolejce, aby zabezpieczyć dostęp do tych strategicznych zasobów niezbędnych do zbudowania przyszłości dla czystej energii. Jednak wyzwania pozostają znaczące i złożone ze względu na ich powiązanie z obecnymi międzynarodowymi mechanizmami bezpieczeństwa energetycznego po tym, jak wiele regionów z dużymi rezerwami REE stało się teatrami napięć geopolitycznych.
Wyzwanie przejścia na odnawialne źródła energii: podejście geopolityczne w świetle międzynarodowej konkurencji o metale ziem rzadkich
Keywords: Rare earth elements; Energy transition; Geopolitical dimensions; International competition; Supply chains; metale ziem rzadkich; transformacja energetyczna; wymiary geopolityczne; międzynarodowa konkurencja; łańcuchy dostaw